URGENSI NASKAH AKADEMIK DALAM PEMBENTUKAN PERATURAN DAERAH DI KABUPATEN NABIRE PROVINSI PAPUA TENGAH - Petrus Tekege (CV. Adiba Aisha Amira, 2023)
This writing aims to provide an understanding that academic texts are the door or window, the breath, the direction for the formation of regional regulations. For this purpose, the researcher uses the normative legal research method and the sociological legal research method, namely a research based on legal sciences, especially constitutional law, which is not only a normative issue but also includes socio-empirical issues, in accordance with phenomena and realities that developed in Nabire-Central Papuan society. In an effort to collect data researchers based on primary data sources and secondary data sources. Based on these data, the authors analyzed using qualitative methods. Based on the research, the results show that there is a lack of regional regulations that begin with the formation of Academic texts which are a participatory form of the community starting from planning, forming, implementing, monitoring and evaluating so that the community is apathetic and accepts every regional regulation as it is established by the regional government. and the Nabire district parliament. For this reason, it is important for the formation of a regional regulation that an academic text is first formed which is then inseparable from the regional regulation. As a mirror academic texts will be effective for regional regulations in their formation. The effectiveness of the enactment of regional regulations is highly dependent on the degree to which the public accepts the enactment of regional regulations. In order for academic papers to become the basic idea of general merit or shared expectations and to be effective, starting from the planning process, the community must be involved so that it does not become a problem, and is accepted by the community in its implementation in the future.